Dental ontogeny and replacement in Pliosauridae. Issue 11 (November 2015) - Sassoon, Judyth; Foffa, Davide; Marek, Ryan
Abstract : Dental morphology and patterns of tooth replacement in representatives of the clade Pliosauridae (Reptilia, Sauropterygia) are evaluated in detail. The jaws of one basal ( Thalassiodracon hawkinsii ) and two derived species ( Pliosaurus carpenteri, Pliosaurus kevani ) were visualized by μCT scans, and the ontogenetic patterns, or 'movement paths', of replacement teeth could be mapped. Other specimens ( Peloneustes philarchus and Pliosaurus westbuyensis ) with well-preserved jaws containing functional and replacement teeth in situ were also examined directly, and waves of tooth replacement could be inferred from the degree of in situ tooth development and the fusion between functional and replacement alveoli. The analysis revealed symmetrical tooth eruption over the medial axis throughout the length of the jaw in the basal pliosaurid Thalassiodracon . By contrast, symmetrical tooth eruption patterns occur only along the anterior sections of the jaws of derived pliosaurids. In Pliosaurus, replacement schedules differ in the anterior and posterior portions of the jaws and appear to correlate with differences in tooth morphology and symmetrical replacement. The anterior teeth exhibit longer replacement cycle periods and symmetrical replacement, while shorter cycle periods and asymmetry are seen posteriorly. A longer period suggests slower replacement and is characteristic of large, specialized caniniform teeth in the longer snouted Late Jurassic taxa. Smaller posterior teeth have a shorter period and therefore a faster replacement cycle. The transition from long to short replacement period over the length of the jaw is thought to account for the loss of symmetry. This differentiation could relate to differential tooth function and a type of heterodonty. We therefore propose a new model of pliosaurid tooth replacement patterns and present it in a phylogenetic context.